2011
DOI: 10.5937/ratpov1101183k
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pea and spring cereals intercropping on grain yield and crude protein content

Abstract: Summary:The advantage of intercropping is benefi cial biological interactions between crops and their different use of growth resources. Our experiment aimed at investigating the effects of pea intercropping with cereals on the improvement of cereal supply with nitrogen and protein content in grain on a loamy soil in organic farming conditions. It was carried out during 2007-2009 at the Lithuanian Institute of Agriculture in Dotnuva. Pea (Pisum sativum L.) and spring wheat (Triticum aestivum L.), spring barley… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Several authors have reported other advantages of intercropping as well: better usage of environmental resources, improved soil fertility and nitrogen increase, less pesticides used, improved forage quality, yield stability and uniformity and finally -an increase in overall production (Sumner et al, 1981;Mousavi & Eskandari;, Kadžiulienė et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Several authors have reported other advantages of intercropping as well: better usage of environmental resources, improved soil fertility and nitrogen increase, less pesticides used, improved forage quality, yield stability and uniformity and finally -an increase in overall production (Sumner et al, 1981;Mousavi & Eskandari;, Kadžiulienė et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The obtained results showed that the grain yield of faba bean and wheat, grown in a sole crop or in the intercrop, significantly varied between two experimental years. Šarūnaitė et al (2010) and Kadžiulienė et al (2011) concluded that grain yield of intercropped species significantly varied between the experimental years.…”
Section: Discussionmentioning
confidence: 99%
“…The investigation of triticale in intercropping with forage crops showed positive effect to grain quality (Lestingi et al, 2010;Nefir and Tabără, 2011). The productivity of spring cereal monocrops and pea/cereal intercrops studied and found that grain yield variate in dependence of genotype of cereal and environmental condition (Kadţiulienė et al, 2011). They found that in some environmental condition grain yield was higher in intercrops and that in pea/cereal intercrop expressed stable yield.…”
Section: Introductionmentioning
confidence: 99%